Integrating the Interpersonal Theory of Suicide Into the Relations Between Cyber-Victimization and Suicidality Among Adolescents: A Short-Term Prospective Study. Issue 1 (January 2023) - Meng, Fanchen; Zhu, Xinxin; Gao, Qianqian; Li, Xiang; Chen, Jing; Sa, Qieer
The relation between cyber-victimization and suicidality among adolescents has been well documented; however, the mechanisms underlying this association have not been well investigated. Drawing upon the interpersonal theory of suicide, this study aimed to examine the mediating mechanisms (i.e., thwarted belongingness and perceived burdensomeness) underlying longitudinal, bidirectional relations between cyber-victimization and suicidal ideation/attempts among adolescents and explore gender differences in the mechanisms. Participants were 497 Chinese adolescents (46.1% male; M age = 13.28, SD = .66), who completed the assessment of cyber-victimization, thwarted belongingness, and perceived burdensomeness, suicidal ideation/attempts at three-time points. The time interval between each two assessments is two weeks. Results showed the reciprocal relations between cyber-victimization and thwarted belongingness/perceived burdensomeness, between thwarted belongingness and suicidal ideation/suicide attempts, and between perceived burdensomeness and suicide attempts. Longitudinal mediation analyses indicated that Time 2 thwarted belongingness mediated the relation between Time 1 cyber-victimization and Time 3 suicidal ideation/suicide attempts. Besides, the reverse pathway from Time 1 suicidal ideation to Time 3 cyber-victimization was also mediated by Time 2 thwarted belongingness, but it was only significant in females, as suggested by multiple-group analyses. According to the aforementioned results, the interpersonal theory of suicide provides a useful framework for understanding relations between cyber-victimization and suicidality. Findings suggest that intervention targeted at improving the need to belong may help reduce suicide risk and lower cyber-victimization. Anti-cyber-victimization should be integrated into suicide intervention and prevention programs, and gender differences should be taken into account in order to enhance the program's effectiveness.